HISTORY FORMATION AND DEVELOPMEN OF STUDENT PRODUCTION BRIGADES IN STAVROPOL REGION - Sergey N. Lyapah; Lyudmila A. Filimonyuk (Вестник Северо-Кавказского федерального университета)
The article examines the questions of labor education development. On the basis of the analysis of the history and experience of advanced pupils production brigades of the Stavropol Territory, offered a program of profile-oriented labor education of pupils village schools in the conditions of PPB.